Effect of Dietary Supplementation of Choline from Different Sources on Performance and Economics of Commercial Broiler Chicken - 1; 2; Savaliya, Fulabhai P.; Patel, Atul B.; Ghasura, Arman S.; Patel, Nishant M.; Rajpura, Rais M. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
An experiment was conducted to investigate the effect of dietary supplementation of choline from different sources on the performanceand economics of commercial broiler chicken. Day old broiler chicks (Vencobb, n=216) were randomly distributed into nine experimentalgroups with four replicates of six birds each. The experimental groups (T1 to T9) were fed with diet containing choline chloride 60%@ 1000 g/ton, 750 g/ton, and 500 g/ton feed in T1 (Control), T2, and T3 ration. Similarly, herbal choline @ 1000 g/ton, 750 g/ton and500 g/ton feed was given in T4,5,6 ration, and phosphatidylcholine @ 1000 g/ton 750 g/ton and 500 g/ton feed-in T7,8,9 ration, respectively.The trial was carried out in deep litter pen for 42 days. During the whole experiment, the mortality pattern of the birds was within thepermissible limits and revealed no adverse effects of feeding choline from different sources in diet. The study results indicated thatthe supplementation of choline chloride 60% @1000 g/ton feed (Control group) showed higher body weight and body weight gaincompared to other rations. Total feed consumption and feed conversion ratio of birds fed with treatment rations supplemented withdifferent choline sources were at par among the rations. The return over feed cost was highest in broilers fed a diet with choline chloride60 % @ 1000 g/ton feed.
Keywords: Broiler; Choline chloride; Economics; Herbal Choline; Performance parameters